PENILAIAN TINGKAT KERENTANAN AIR TANAH TERHADAP PENCEMARAN MENGGUNAKAN METODE SINTACS DI KECAMATAN MEGALUH KABUPATEN JOMBANG - Susrama, Fadlil Adya; Siswoyo, Hari; Sayekti, Rini Wahyu (Universitas Lambung Mangkurat, 2024)
An area of 1,853 ha (65.2%) of land in Megaluh District is used for rice fields. Pesticides and inorganic fertilizers are widely used as plant fertilizers in Megaluh District, where excessive use in rice fields can pollute the groundwater below. This research is aimed at identifying spatially the possibility of groundwater pollution using the hydrogeological approach of the SINTACS method. The SINTACS method has five scenarios that produce different weights for each parameter that can cause groundwater vulnerability. The data used in the SINTACS method are groundwater depth, infiltration rate, unsaturated zone, soil texture, aquifer media, hydraulic conductivity and topography. This research uses variations in the depth of the groundwater level to determine the trend in the level of groundwater vulnerability in Megaluh District during the rainy season and dry season with a severe impact scenario as an approach to environmental conditions in Megaluh District. The results of the analysis show that the level of groundwater vulnerability in Megaluh District is in the range of 143.6 (rather high) – 198 (high). The percentage of rice field area which reached 65.2% resulted in a rather high level of vulnerability of 42.35% and a high level of vulnerability of 57.65%.